5TH TO 9TH GRADE TEAM SPORTS IN PRIVATE ELEMENTARY SCHOOLS, IN THE CITY OF BAGÉ, RIO GRANDE DO SUL. (Fiep Bulletin - online, 2016)
The theme of this research was chosen with the intention of alerting and warning students and teachers of the importance of team sports in Physical Education, aiming to work on team sports reviewing basic teachings of all of them, not focusing only on the ones sought by the majority. The objectives of this research are: to analyze the teaching of team sports from 5th to 9th grade in Private Elementary Schools in the city of Bagé-RS, from the Physical Education teachers perspective; to identify the team sports taught in Elementary Education; to verify the subjects developed during the school year and approximate the methodology used by teachers. This research is of qualitative descriptive character. Teachers and students from 5th to 9th grade from two Private Elementary Schools in the city of Bagé-RS were interviewed, as well as physical activities related to team sports in the respective grades in the participant schools were observed, during a two-week period, consisting of four weekly lessons. The assessment of information was carried out through content analysis technique and data source triangulation. When finishing this study, the following categories were identified after analysis of information collected during the empirical phase of observations: The Teaching of Sport; and the subcategories: Team Sports and subjects developed; the methodology used. Utilizing thus, observations from two schools and interviews with Physical Education teachers, where there were found compatibilities and contradictions, related to field evidence, researcher's observations and views of scholars on the subject. Therefore, it was understood in the study that team sports are taught in schools, but in a traditional way, with a structure in lessons, and with methodological and evaluation means varying according to their teacher. Keywords: team sports; Physical Education, school, Elementary Education.
Keywords: School Physical Education. Collective sports. Elementary School.